Anti-inflammatory sesquiterpenes from the medicinal herb Tanacetum sinaicum1. Issue 56 (19th June 2015) - Hegazy, Mohamed-Elamir F.; Hamed, Ahmed R.; Mohamed, Tarik A.; Debbab, Abdessamad; Nakamura, Seikou; Matsuda, Hisashi; Paré, Paul W.
<x xml:space="preserve">Abstract</x> New sesquiterpenes tanacetolide A–C (1–3) were isolated from a Tanacetum sinaicum extract together with known compounds (4–10).